Prognostic Value of Venous Invasion Detected by Elastin Stain May Surpass Lymph Node Status in Colon Cancer. Issue 8 (August 2021) - Kim, Hye Jin; Choi, Gyu-Seog; Seo, An Na; Park, Jun Seok; Park, Soo Yeun; Cho, Seung Hyun; Yoon, Ghilsuk
Abstract : BACKGROUND: Venous invasion is a poor prognostic factor in colon cancer but is often underreported with significant variability. OBJECTIVES: We aimed to determine the impact of an elastin stain on venous invasion detection in colon cancer and evaluate the value of venous invasion in predicting disease recurrence in combination with lymph node status and other prognostic factors. DESIGN: This is a retrospective analysis of a prospectively collected database. SETTING: This study was conducted at a tertiary cancer center. PATIENTS: A total of 418 patients who underwent curative resection for stage I to III colon cancer and routinely adopted an elastin stain were evaluated. MAIN OUTCOME MEASURES: Venous invasion detection rate after adopting elastin stain, prognostic factors influencing disease recurrences by multivariate Cox regression models, and survival were measured. The zones of lymph node metastasis were defined as LNZ1, LNZ2, and LNZ3, corresponding to metastases in the pericolic, intermediate, and apical nodes. RESULTS: Venous invasion detection rate increased from 11.3% to 35.4% compared with the previous period in which only hematoxylin and eosin stain was performed. Cox regression analysis showed venous invasion (HR, 3.856; 95% CI, 1.249–11.910; p = 0.019) and lymph node metastases (HR, 3.156; 95% CI, 1.094–9.108; p = 0.034) in all stages and LNZ 2, 3 (HR, 2.649; 95% CI, 1.244–5.640; p = 0.012) in stage III to be significantly associated with poor disease-free survival. When stratifying all patients by these 3 factors, patients with stage III [LNZ1/venous invasion (–)] had disease-free survival comparable with stage I, but significantly better disease-free survival than those with stage II [venous invasion (+)] ( p = 0.018). Patients with stage II [venous invasion (+)] had better disease-free survival by using adjuvant chemotherapy ( p < 0.001). LIMITATIONS: This study was limited by its retrospective design. CONCLUSION: Elastin stain contributed to a considerable increase in venous invasion detection. Venous invasion can be a powerful predictor of poor disease-free survival beyond lymph node metastases when limited to the pericolic area and is useful for deciding the use of adjuvant chemotherapy in stage II colon cancer. See Video Abstract at http://links.lww.com/DCR/B573 . EL VALOR PRONÓSTICO DE LA INVASIÓN VENOSA DETECTADA POR LA TINCIÓN DE ELASTINA PUEDE SUPERAR EL ESTADO DE LOS GANGLIOS LINFÁTICOS EN EL CÁNCER DE COLON: ANTECEDENTES: Invasión venosa (IV) es un factor de mal pronóstico en el cáncer de colon, que frecuentemente no se informa con una variabilidad significativa. OBJETIVOS: Nuestro objetivo fue determinar el impacto de tinción de elastina en la detección de IV en el cáncer de colon y evaluar el valor de IV en la predicción de la recurrencia de la enfermedad en combinación con el estado de los ganglios linfáticos y otros factores pronósticos. DISEÑO: Este es un análisis retrospectivo de una base de datos recopilada prospectivamente. ENTORNO CLINICO: Este estudio se realizó en un centro oncológico de referencia de tercer nivel. PACIENTES: Se valoraron un total de 418 pacientes sometidos a resección curativa por cáncer de colon en estadio I-III utilizando de manera rutinaria una tinción de elastina. PRINCIPALES MEDIDAS DE VALORACION: Se midieron la tasa de detección de IV después de adoptar la tinción de elastina, los factores de pronóstico que influyen en las recurrencias de la enfermedad mediante modelos de regresión de Cox multivariados y la supervivencia. La zona de metástasis ganglionares se definió como, LNZ1, LNZ2 y LNZ3, correspondientes a las metástasis en los ganglios pericólicos, intermedios y apicales, respectivamente. RESULTADOS: La tasa de detección de IV aumentó de 11, 3% a 35, 4% en comparación con el período anterior en el que solo se realizó tinción con hematoxilina y eosina. El análisis de regresión de Cox mostró VI (razón de riesgo, 3.856; intervalo de confianza [IC] del 95%, 1.249-11.910, p = 0.019) y metástasis en los ganglios linfáticos (razón de riesgo, 3.156; IC del 95%, 1.094-9.108, p = 0.034) en todos los estadios y LNZ 2, 3 (cociente de riesgo, 2.649; IC del 95%, 1.244-5.640, p = 0.012) en el estadio III se asociaron significativamente con una pobre supervivencia libre de enfermedad. Al estratificar a todos los pacientes según estos tres factores, los pacientes con estadio III [LNZ1 / VI (-)] tuvieron una sobrevivencia sin enfermedad (SSE) comparable con el estadio I, pero una supervivencia libre de enfermedad significativamente mejor que aquellos con estadio II [VI (+)] ( p = 0, 018). Pacientes en estadío II [VI (+)] tuvieron una mejor supervivencia sin enfermedad mediante el uso de quimioterapia adyuvante ( p <0, 001). LIMITACIONES: Estudio limitado por su diseño retrospectivo. CONCLUSIÓN: La tinción de elastina contribuyó a un aumento considerable en la detección de IV. IV puede ser un poderoso predictor de supervivencia sin enfermedad deficiente más allá de las metástasis de los ganglios linfáticos cuando se limita al área pericólica y es útil para decidir el uso de quimioterapia adyuvante en el cáncer de colon en estadío II. Consulte Video Resumen en http://links.lww.com/DCR/B573 . (Traducción—Dr. Adrian Ortega )